A multi-disciplinary education process related to the discharging of children from hospital when the child has been diagnosed with type 1 diabetes - a qualitative study - Hallström Inger; Jönsson Lisbeth; Lundqvist Anita (BMC, 2010)
Abstract Background Worldwide, insulin-dependent type 1 diabetes is one of the most frequently diagnosed long-term endocrine disorders found in children and the incidences of this diseased is still increasing. In Sweden the routines are, according to national guidelines, when the child is diagnosed with type 1 diabetes, the child and its family remains at the hospital for about two weeks. There is limited knowledge about how a diabetes team handles a child and its family from admission to discharge, therefore the purpose of this study was to seek a deeper understanding of how the diabetes team's parent/child education process works, from admission to discharge, among families with a child newly diagnosed with type 1 diabetes. Methods Qualitative data collection was used. Four focus-group interviews, with a sample of three diabetes teams from different paediatric hospitals in the south western part of Sweden, were conducted and the data recorded on tape and then analysed using qualitative content analysis. Results The results indicate that achieving a status of self-care on the part of the patient is the goal of the diabetes education programme. Part of the programme is aimed at guiding the child and its parents towards self-help through the means of providing them with knowledge of the disease and its treatment to enable the whole family to understand the need for cooperation in the process. To do this requires an understanding, by the diabetes team, of the individualities of the family in order to gain an overall picture. Conclusion The results of this study show that the diabetes education programme is specifically designed for each family using the internationally recommended clinical practice guidelines with its specific aims and objectives. Achieving the families' willingness to assist in the self-care of the child care is the goal of the parent education process. To achieve this, the paediatric diabetes specialist nurse and the diabetes specialist paediatrician immediately and deliberately start the process of educating the family using a programme designed to give them the necessary knowledge and skills they will need to manage their child's type 1 diabetes at home.